MHC class II super-enhancer increases surface expression of HLA-DR and HLA-DQ and affects cytokine production in autoimmune vitiligo - Cavalli, Giulio (Proc Natl Acad Sci U S A, 2016)
Genetic risk for autoimmunity in HLA genes is most often attributed to structural specificity resulting in presentation of self-antigens. Autoimmune vitiligo is strongly associated with the MHC class II region. Here, we fine-map vitiligo MHC class II genetic risk to three SNPs only 47 bp apart, located within a predicted super-enhancer in an intergenic region between HLA-DRB1 and HLA-DQA1, localized by a genome-wide association study of 2,853 Caucasian vitiligo patients. The super-enhancer corresponds to an expression quantitative trait locus for expression of HLA-DR and HLA-DQ RNA; we observed elevated surface expression of HLA-DR (P = 0.008) and HLA-DQ (P = 0.02) on monocytes from healthy subjects homozygous for the high-risk SNP haplotype. Unexpectedly, pathogen-stimulated peripheral blood mononuclear cells from subjects homozygous for the high-risk super-enhancer haplotype exhibited greater increase in production of IFN-γ and IL-1β than cells from subjects homozygous for the low-risk haplotype. Specifically, production of IFN-γ on stimulation of dectin-1, mannose, and Toll-like receptors with Candida albicans and Staphylococcus epidermidis was 2.5- and 2.9-fold higher in high-risk subjects than in low-risk subjects, respectively (P = 0.007 and P = 0.01). Similarly, production of IL-1β was fivefold higher in high-risk subjects than in low-risk subjects (P = 0.02). Increased production of immunostimulatory cytokines in subjects carrying the high-risk haplotype may act as an “adjuvant” during the presentation of autoantigens, tying together genetic variation in the MHC with the development of autoimmunity. This study demonstrates that for risk of autoimmune vitiligo, expression level of HLA class II molecules is as or more important than antigen specificity.